High-wet-skid-resistance and low-noise electric automobile tire and preparation method thereof

By using modified fillers and optimizing the formulation of rubber composition, the problem of tires being difficult to take into account low noise and high anti-slip resistance is solved, and the tires are excellent mechanical properties, anti-slip properties and noise reduction properties are achieved.

CN119463313AActive Publication Date: 2025-02-18SHANDONG HUASHENG RUBBER +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411425093.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-18
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The prior art is difficult to take into account the low noise and high anti-slip properties of tires, and the existing improvement methods are mainly focused on the one direction of noise or anti-slip.

Method used

Fillers prepared by hybrid cross-linking modification of carbon black and carbon nanotubes by 4-hydroxybutyl acrylate glycidyl ether, unsaturated anhydride and cashew phenol, combined with natural rubber and polystyrene butadiene rubber, optimize rubber The composition is formulated to improve the mechanical properties, anti-slip properties and noise reduction properties of the tire.

Benefits of technology

The tires have excellent mechanical properties, high anti-slip properties and noise reduction performance, and the noise can be reduced to less than 60dB, and the effect is long-lasting.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081921190000061
    Figure BDA0005081921190000061
  • Figure BDA0005081921190000062
    Figure BDA0005081921190000062
  • Figure BDA0005081921190000071
    Figure BDA0005081921190000071
Patent Text Reader

Abstract

The invention provides a high-wet-skid-resistance and low-noise electric automobile tire and a preparation method thereof, and relates to the technical field of tire preparation. The high-wet-skid-resistance and low-noise electric automobile tire comprises a tire tread made of a rubber composition, the rubber composition comprises a rubber component and a filler, and the filler is prepared by performing hybrid cross-linking modification on carbon black and carbon nanotubes by using 4-hydroxybutyl acrylate glycidyl ether, unsaturated anhydride and cardanol. By controlling the formula of the tread rubber and the tire structure, the obtained tire has excellent mechanical properties, high wet skid resistance and noise reduction performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tire preparation, and in particular to a highly slip-resistant and low-noise electric vehicle tire and a preparation method thereof. Background Art

[0002] At present, cars have become an indispensable means of transportation in people's lives. With the development of the automobile industry, people have put forward higher requirements on the handling safety, fuel efficiency and comfort of tires during driving, such as handling safety, low energy consumption, comfort, etc. Therefore, clear performance requirements have been formulated for the wet grip ability, rolling resistance and noise of tires.

[0003] When a car is driving at high speed, it will generate noise, and the noise generated by the tire is particularly important. The tire noise of the car will affect the driving experience of the driver. Therefore, people expect to get a low-noise tire. But at the same time, the safety of the car must be guaranteed, which requires that the overall operating stability of the tire cannot be sacrificed.

[0004] To address the above issues, some research progress has been made. For example, the wet grip performance is improved by using solution-polymerized styrene-butadiene rubber and the wet grip performance is further balanced by using composite polyisoprene rubber. Another example is that the polyurethane foam prepared by changing the content of the foaming agent is placed in the inner cavity of the pneumatic tire, which has the effect of reducing the resonance noise generated in the inner cavity of the tire and improving the durability.

[0005] However, the above method has only improved the noise or anti-skid of the tire. Therefore, how to take into account the low noise and high anti-skid of the tire is still a problem to be solved urgently by those skilled in the art. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention provides a highly anti-slip and low-noise electric vehicle tire and a preparation method thereof.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] A highly anti-slip and low-noise electric vehicle tire, comprising a tread formed of a rubber composition; wherein:

[0009] The rubber composition comprises a rubber component and a filler;

[0010] The filler is prepared by hybrid cross-linking and modifying carbon black and carbon nanotubes with 4-hydroxybutyl acrylate glycidyl ether, unsaturated acid anhydride and cardanol.

[0011] In a further embodiment, the rubber component is selected from any one or more of natural rubber, solution polymerized styrene butadiene rubber, and butadiene rubber; preferably, it is a combination of natural rubber and solution polymerized styrene butadiene rubber, and the mass ratio of the two is (50-60):(40-50).

[0012] In a further embodiment, the mass ratio of carbon black to carbon nanotubes in the filler is (5-7.5):(2.5-5), and the preferred mass ratio is 7.2:2.8.

[0013] In a further embodiment, the particle size of the carbon black is 100 nm to 600 nm.

[0014] In a more preferred embodiment, the carbon black has a particle size of 400 nm.

[0015] In a further embodiment, the carbon nanotubes are multi-walled carbon nanotubes, and the outer diameter of the carbon nanotubes is 10 to 30 nm and the length is 5 to 15 μm.

[0016] In a further embodiment, the amount of 4-hydroxybutyl acrylate glycidyl ether in the filler is 5-8% of the total mass of carbon black and carbon nanotubes, preferably 6% of the total mass of carbon black and carbon nanotubes.

[0017] In a further embodiment, the unsaturated acid anhydride in the filler is selected from any one or more of acrylic anhydride, itaconic anhydride, and maleic anhydride, preferably maleic anhydride; the amount of the unsaturated acid anhydride is 15-20% of the total mass of the carbon black and the carbon nanotubes, preferably 16% of the total mass of the carbon black and the carbon nanotubes.

[0018] In a further embodiment, the amount of cardanol in the filler is 5-10% of the total mass of the carbon black and the carbon nanotubes, preferably 7% of the total mass of the carbon black and the carbon nanotubes.

[0019] In a further embodiment, the filler is prepared by the following method:

[0020] (1) treating carbon nanotubes and carbon black with concentrated sulfuric acid respectively;

[0021] (2) mixing cardanol and unsaturated acid anhydride, adding sulfuric acid as a catalyst, reacting at 200-210° C. for 2-3 hours, cooling to 70-80° C., adding 4-hydroxybutyl acrylate glycidyl ether and reacting for 24-48 hours to obtain a copolymer solution;

[0022] (3) The copolymer solution is mixed with the carbon black and carbon nanotubes pretreated in step (1), subjected to ultrasonic treatment, an initiator is added, and the mixture is reacted at 150-155° C. for 1-2 hours to obtain the filler.

[0023] Preferably, in step (1), the treatment step is: respectively placing carbon nanotubes and carbon black in a sulfuric acid solution with a mass fraction of 5 to 20%, ultrasonically treating for 30 to 60 minutes, and taking out and drying after the treatment.

[0024] Preferably, in step (2), the amount of sulfuric acid used is 0.5-5% of the total mass of the reactants.

[0025] Preferably, in step (3), the initiator is selected from azo initiators and peroxide initiators; the added amount of the initiator is 0.5 to 3% of the total mass of the reactants.

[0026] In a further embodiment, the rubber composition further comprises any one or more of stearic acid, zinc oxide, an antioxidant, a vulcanizing agent, and an accelerator.

[0027] Preferably, the antioxidant is selected from any one or more of antioxidant DNP, antioxidant 4020, antioxidant TMQ, and antioxidant BLE.

[0028] Preferably, the accelerator is selected from any one or more of dithiocarbamate accelerators, aldehyde amine accelerators, thiuram accelerators, sulfenamide accelerators, thiazole accelerators and xanthate accelerators.

[0029] Preferably, the vulcanizing agent is sulfur.

[0030] The rubber composition comprises the following raw materials in parts by weight: 100 parts of rubber component, 40-60 parts of filler, 1-5 parts of stearic acid, 2-6 parts of zinc oxide, 1-5 parts of antioxidant, 1-3 parts of vulcanizer, and 2-5 parts of accelerator.

[0031] Preferably, the rubber composition comprises the following raw materials in parts by weight: 100 parts of rubber component, 55 parts of filler, 2 parts of stearic acid, 4 parts of zinc oxide, 3.5 parts of antioxidant, 2.5 parts of vulcanizer, and 3 parts of accelerator.

[0032] In a further embodiment, the highly anti-skid and low-noise electric vehicle tire also includes a carcass, a sidewall, a belt layer and a bead.

[0033] Preferably, the belt layer is arranged between the tread and the carcass, and the material of the belt layer is steel cord.

[0034] Preferably, the carcass is made of aramid fiber and / or nylon fiber.

[0035] Further preferably, the surface of the steel cords in the belt layer is also coated with rubber, and the mass of the rubber is 0.1-5% of the steel cords.

[0036] The rubber material comprises the following raw materials in percentage by weight: 100 parts of natural rubber, 5-15 parts of polyurethane resin, 40-55 parts of carbon black, 2-5 parts of basalt fiber, 3-8 parts of sulfur, 0.5-2 parts of accelerator, 1-5 parts of antioxidant, and 0.5-1.5 parts of cobalt borate.

[0037] On the other hand, the method for preparing the above-mentioned high anti-slip and low-noise electric vehicle tire comprises the following steps:

[0038] The rubber composition is kneaded to obtain a mixed rubber, which is then pressurized and vulcanized at 160-180° C. to obtain a vulcanized rubber, which is made into a tread to prepare a lightweight, high-strength and low rolling resistance tire for new energy vehicles.

[0039] In a further embodiment, the rubber composition mixing step comprises:

[0040] The materials except the vulcanizing agent and the accelerator are mixed at 140-150° C. for 3-5 minutes, and then the vulcanizing agent and the accelerator are added and mixed at 130-145° C. for 1-2 minutes to obtain a mixed rubber.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] 1. The high anti-skid and low-noise electric vehicle tire of the present invention optimizes the formula of the tread rubber so that the obtained tire has excellent mechanical properties, high anti-skid performance and noise reduction performance.

[0043] 2. Compared with the traditional method of using carbon black as reinforcing filler, the tread rubber of the present invention uses a filler obtained by hybrid cross-linking modification of carbon black and carbon nanotubes with 4-hydroxybutyl acrylate glycidyl ether, unsaturated acid anhydride and cardanol instead of carbon black. The compatibility of the modified carbon black and carbon nanotubes with the rubber component is improved, and the components work together to make the resulting tire have excellent mechanical properties, high anti-skid performance and noise reduction performance.

[0044] 3. Carbon nanotubes are added to the filler of the present invention to replace part of the carbon black. The combination of carbon nanotubes and carbon black helps to improve the strength of the tire and increase the noise reduction performance.

[0045] 4. The filler of the present invention is modified with 4-hydroxybutyl acrylate glycidyl ether, unsaturated acid anhydride and cardanol, and the modifier forms a cross-linked structure on the surface. On the one hand, the dispersibility in the rubber component is increased, thereby exerting the reinforcing effect of carbon black and carbon nanotubes; on the other hand, the three modifiers form a multi-cross-linked structure after modifying the filler, which helps to improve the tire's function of absorbing and isolating noise, has excellent noise reduction performance, and can increase wet skid resistance; especially when the ratio of the three modifiers is limited, it can ensure that the rubber composition can give full play to its strength and toughness and improve its mechanical properties. In addition, it can also ensure that the noise reduction of the tire is more lasting and the noise is kept below 60dB.

[0046] 5. The present invention has the characteristics of simple operation, strong safety, strong practicality and suitability for popularization and use. DETAILED DESCRIPTION

[0047] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.

[0048] The present invention is further described below by way of specific examples. Unless otherwise specified, the various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels.

[0049] Embodiments 1 to 4

[0050] A rubber composition, the specific components of which are shown in Table 1 below, in parts by weight.

[0051] Table 1

[0052] Element Example 1 Example 2 Example 3 Example 4 Natural rubber 60 50 50 40 Solution Polymerized Styrene Butadiene Rubber 40 50 50 60 Stearic acid 1 2 5 2 Zinc Oxide 2 4 6 4 Antioxidant DNP 1 3.5 5 3.5 sulfur 1 2.5 3 2.5 Thiazole vulcanization accelerator MBTS 2 3 5 3 filler 60 55 40 55

[0053] The filler is prepared by the following method (the specific raw material amounts are shown in Table 2 below, in parts by weight):

[0054] (1) respectively placing carbon nanotubes and carbon black in a 10% sulfuric acid solution, ultrasonically treating for 30 minutes, and then taking out and drying them after the treatment;

[0055] (2) mixing cardanol and unsaturated acid anhydride, adding sulfuric acid (0.1% of the total mass of the reactants) as a catalyst, reacting at 200° C. for 3 h, cooling to 70° C., adding 4-hydroxybutyl acrylate glycidyl ether and reacting for 48 h to obtain a copolymer solution;

[0056] (3) adding the carbon black and carbon nanotubes pretreated in step (1) to the copolymer solution of step (2), ultrasonically treating, adding 0.5% by weight of azobisisobutyronitrile, reacting at 150° C. for 2 h, taking out, washing, and drying to obtain a filler.

[0057] Table 2

[0058]

[0059] This embodiment also provides a method for preparing the rubber composition, comprising the following steps:

[0060] The natural rubber, solution polymerized styrene-butadiene rubber and filler are mixed and kneaded at 140°C for 3 minutes; then mixed with stearic acid, zinc oxide, antioxidant and anti-scorch agent, and kneaded at 130°C for 2 minutes; then sulfur and accelerator are added, and kneaded at 120°C for 120 seconds to obtain a mixed rubber.

[0061] Embodiments 5 to 8

[0062] This embodiment is basically the same as Embodiment 2, except that the ratio of carbon black to carbon nanotubes and the ratio of modifier in the filler preparation process are different. The specific raw material amounts are shown in Table 3 below (by weight).

[0063] Table 3

[0064]

[0065]

[0066] Comparative Examples 1 to 4

[0067] This comparative example is basically the same as Example 2, except that the raw materials used in the preparation of the filler are different (by weight), as shown in Table 4 below.

[0068] Table 4

[0069] raw material Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Carbon Black 55 39.6 39.6 39.6 Carbon Nanotubes —— 15.4 15.4 15.4 4-Hydroxybutyl acrylate glycidyl ether 3.3 —— 3.3 3.3 Maleic anhydride 8.8 8.8 —— 8.8 Cardanol 3.85 3.85 3.85 ——

[0070] Comparative Example 5

[0071] This comparative example is substantially the same as Example 2, except that the filler in this comparative example is replaced by an equal amount of carbon black.

[0072] Test Example 1

[0073] The mixed rubber obtained in the above examples and comparative examples was vulcanized at 161° C. for 20 min using a flat vulcanizer to obtain vulcanized rubber, and the following tests were performed:

[0074] 1. Mechanical properties test: tensile properties test is carried out according to standard GB / T528-2009.

[0075] 2. Vibration characteristic index: The sulfur rubber composition was cut into predetermined sizes, and its loss coefficient (η) at 23° C. was measured using a central vibrator produced by B&K. The loss coefficient measured in Comparative Example 5 was set to 100, and the percentage of the loss coefficients of the remaining groups to Comparative Example 5 was expressed as a vibration characteristic index. A higher index indicates better road noise reduction performance (noise reduction performance).

[0076] 3. Dynamic analysis test (DMA): The test conditions are: tensile mode; frequency, 12 Hz; static strain 7%, dynamic strain 0.25%; temperature rise, 2°C / min.

[0077] The test results are shown in Table 5 below.

[0078] Table 5

[0079] Group Tensile strength(MPa) Elongation(%) Vibration characteristic index tanδ@60℃ tanδ@0℃ Example 1 22.7 501 121 0.059 0.814 Example 2 23.8 519 126 0.051 0.821 Example 3 23.5 513 124 0.054 0.816 Example 4 21.3 469 114 0.068 0.794 Example 5 20.7 485 117 0.083 0.788 Example 6 21.2 471 122 0.072 0.750 Example 7 20.3 427 116 0.078 0.684 Example 8 20.1 441 118 0.070 0.731 Comparative Example 1 21.3 468 113 0.074 0.731 Comparative Example 2 20.1 420 108 0.096 0.658 Comparative Example 3 20.8 405 104 0.104 0.610 Comparative Example 4 21.0 412 107 0.092 0.633 Comparative Example 5 18.9 382 100 0.112 0.504

[0080] As shown in the table, the tensile strength of the rubber composition prepared by the formula and preparation method defined by the present invention is more than 23MPa, the fracture test green can reach more than 500%, and the tensile performance is excellent. Compared with Example 2, the tensile strength and elongation of Comparative Examples 1 to 5 are significantly reduced, and the tensile performance is deteriorated. From the results of the vibration characteristic index, compared with Comparative Example 5, the vibration characteristic index of the rubber composition of Comparative Examples 1 to 4 is improved, and the noise reduction performance is improved. It can be seen that compared with carbon black, the use of the filler provided by the present invention to replace it helps to improve the noise reduction performance of the material; the vibration characteristic index of the rubber composition of the embodiment reaches more than 120, up to 128, and the noise reduction performance is excellent. From the dynamic analysis test data, compared with Comparative Example 5, the tanδ@60℃ data of the rubber composition of Comparative Examples 1 to 4 decreases, the tanδ@0℃ data increases, and the anti-wet skid ability is improved, indicating that compared with carbon black, the use of the filler provided by the present invention to replace it helps to improve the anti-wet skid performance of the material; the rubber composition of the embodiment has a low tanδ@60℃ value and a high tanδ@0℃ value, and the anti-wet skid ability is excellent.

[0081] Example 9

[0082] The vulcanized rubbers obtained in the above Examples 1 to 8 and Comparative Examples 1 to 5 were made into tires and their effects were evaluated. The tire specifications were 225 / 55R17 97W. The tires obtained were specifically numbered as follows: the tires obtained using Examples 1 to 8 were marked as tires 1 to 8#, and the tires obtained using Comparative Examples 1 to 5 were marked as tires 9 to 13#.

[0083] Example 10

[0084] The difference from Example 9 is that the surface of the steel cord of the belt layer is coated with 0.5% rubber, the rubber comprising 100 parts of natural rubber, 5 parts of polyurethane resin, 5 parts of basalt fiber, 55 parts of carbon black, 3 parts of sulfur, 0.5 parts of thiazole vulcanization accelerator MBTS, 1 part of antioxidant DNP, and 0.5 parts of cobalt borate; a tire of the same specification is made, recorded as tire 14#.

[0085] The rubber compound used in the belt layer without adding basalt fiber was used as a comparison, and the resulting tire was recorded as tire 15#.

[0086] Test Example 2

[0087] The noise reduction performance of the above tires 1 to 17# was tested: the noise was tested in accordance with GB / T32789-2016 "Tire Noise Test Method Drum Method"; after the test, the tires were drummed for 48 hours under the same conditions, left to stand for 12 hours, and then the noise test was conducted again.

[0088] The test results are shown in Table 7 below.

[0089] Table 7

[0090]

[0091]

[0092] As shown in the table, the noise of the tires prepared by the formula and preparation method defined in the present invention can reach 60db or less, with low noise, excellent noise reduction performance and stable and long-lasting. Compared with tire 2#, tires 9 to 13# have loud noise and significantly lower noise reduction effect than tire 2#. The initial noise of tire 14# is equivalent to that of Example 2, but the noise is lower than that of Example 2 after 48h. The rubber material of the belt layer in tire 15# is different from that of tire 14#, and its noise reduction effect is significantly lower than that of tire 14#. This may be because basalt fiber is added to the rubber material to form a tiny pore structure, which helps to increase the absorption of noise, and the microporous structure of the material is stable, so it can maintain long-lasting noise reduction performance.

[0093] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A highly anti-slip and low-noise electric vehicle tire, characterized in that: Comprising a tread made of a rubber composition; wherein, The rubber composition comprises a rubber component and a filler; The filler is prepared by hybrid cross-linking and modifying carbon black and carbon nanotubes with 4-hydroxybutyl acrylate glycidyl ether, unsaturated acid anhydride and cardanol.

2. The electric vehicle tire with high anti-slip and low noise according to claim 1, characterized in that: The rubber component is selected from any one or more combinations of natural rubber, solution polymerized styrene butadiene rubber, and butadiene rubber; the rubber component is preferably a combination of natural rubber and solution polymerized styrene butadiene rubber in a mass ratio of (50-60):(40-50).

3. The electric vehicle tire with high anti-slip and low noise according to claim 1, characterized in that: The mass ratio of carbon black to carbon nanotubes in the filler is (5-7.5):(2.5-5), and the preferred mass ratio is 7.2:2.

8.

4. The electric vehicle tire with high anti-slip and low noise according to claim 1, characterized in that: The unsaturated acid anhydride is selected from any one or more of acrylic anhydride, itaconic anhydride and maleic anhydride, preferably maleic anhydride.

5. The electric vehicle tire with high anti-slip and low noise according to claim 1, characterized in that: The amount of 4-hydroxybutyl acrylate glycidyl ether in the filler is 5-8% of the total mass of carbon black and carbon nanotubes, preferably 6% of the total mass of carbon black and carbon nanotubes; The amount of the unsaturated anhydride is 15-20% of the total mass of the carbon black and the carbon nanotubes, preferably 16% of the total mass of the carbon black and the carbon nanotubes; The amount of cardanol used is 5-10% of the total mass of carbon black and carbon nanotubes, preferably 7% of the total mass of carbon black and carbon nanotubes.

6. The electric vehicle tire with high anti-skid and low noise according to claim 1, characterized in that: The rubber composition further comprises any one or more of stearic acid, zinc oxide, antioxidant, vulcanizing agent and accelerator.

7. The electric vehicle tire with high anti-slip and low noise according to claim 5, characterized in that: The rubber composition comprises the following raw materials by weight: 100 parts of rubber component, 40-60 parts of filler, 1-5 parts of stearic acid, 2-6 parts of zinc oxide, 1-5 parts of antioxidant, 1-3 parts of vulcanizer and 2-5 parts of accelerator.

8. The electric vehicle tire with high anti-slip and low noise according to claim 5, characterized in that: The highly anti-slip and low-noise electric vehicle tire also includes a carcass, a sidewall, a belt layer and a tire bead; the belt layer is arranged between the tread and the carcass, and the material of the belt layer is steel cord.

9. The method for preparing a highly anti-slip and low-noise electric vehicle tire according to any one of claims 1 to 8, characterized in that: The following steps are involved: The rubber composition is kneaded to obtain a mixed rubber, which is then pressurized and vulcanized at 160-180° C. to obtain a vulcanized rubber, which is made into a tread to prepare a lightweight, high-strength and low rolling resistance tire for new energy vehicles.

10. The method for preparing a highly anti-slip and low-noise electric vehicle tire according to claim 9, characterized in that: The rubber composition mixing step comprises: The materials except the vulcanizing agent and the accelerator are mixed at 140-150° C. for 3-5 minutes, and then the vulcanizing agent and the accelerator are added and mixed at 130-145° C. for 1-2 minutes to obtain a mixed rubber.

Citation Information

Patent Citations

  • Photocuring oligomer, preparation method thereof, fabric surface treatment liquid containing same, and using method of fabric surface treatment liquid

    CN109535303A

  • Sole nano anti-skid layer and preparation method thereof

    CN112552568A

  • Tread rubber for high-speed tire and preparation method of tread rubber

    CN115850828A

  • Epoxy functionalized polysulfide modified white carbon black / rubber composite material and preparation method thereof

    CN116554561A

  • Tread rubber with noise reduction performance, preparation method of tread rubber and tire

    CN116656021A